Effect of decellularization on the structural and mechanical properties of porcine valvular matrices. - Wong, Jason Pingshun. (2009)
Tissue engineered valves have the potential of being an ideal valve substitute for transplants, as research shows that mechanical valves carry the risk of thromboembolism. Unlike mechanical heart valves, tissue engineered valves possess excellent hemodynamics qualities, and shares the same biomechanical properties that is desired in native aortic heart valves. However, tissue engineered valves obtained are prone to structural degradation resulting limited durability when implanted. As such, the effects of decellularization on the biomechanical property of tissue engineered valves are actively researched upon. The objective of this project is to characterize the structural and the biomechanical properties of decellularized aortic heart valves and the aim of this project is to co-relate the mechanical property of decellularized aortic valves with quantified amounts of collagen and glycosaminoglycans (GAGs). This study performed seeks to address the contradictory and inconclusive data that exists in literature and hopes to determine the relationship between the mechanical property and the biochemical components that exist within the decellularized heart valves. Heart valves that were decellularized showed a change in surface morphology, mechanical property such as Young’s Modulus and Maximum Load, and the amounts of collagen and GAGs. It is shown that apart from the direct co-relation between the mechanical property and the amounts of collagen and GAGs present and it is concluded that a synergistic relationship does exist between collagen and GAGs in heart valves decellularized by Triton X-100.This translates to the closest resemblance of mechanical properties as compared to native aortic valves, making it the most suitable decelluarizing agent.